ANALYSIS OF PPK PERFORMANCE THROUGH COMPETENCE AND MOTIVATION IN THE SAKTI APPLICATION AT MABESAL - Zunaedi, Ranu Marmono; Suharjo, Bambang; Prasetyo, Aribowo sudiantomo (IJOSMAS, 2024)
This study analyzes the performance of Commitment Making Officers (PPK) through competence and motivation in the use of the Agency-Level Financial Application System (SAKTI) at the Indonesian Navy Headquarters. In the implementation of the budget and management of state finances, PPK plays a strategic role in ensuring efficiency, transparency, and accountability in the procurement of goods and services. PPK performance is often influenced by the level of competence and motivation they have. PPK competence not only includes regulatory knowledge, but also technical and managerial skills. High motivation is also an important factor in driving optimal performance. This study uses a combination of quantitative and qualitative methods with sequential explanatory. Through questionnaires and interviews, data from 26 PPKs in the Navy Headquarters environment were processed using SPSS and NVivo. The results of the analysis show that PPK competence and motivation have a significant influence on performance in the use of SAKTI. Based on these results, recommendations in the form of increasing performance-based training, mentoring, and awards are proposed to improve the effectiveness of SAKTI use and PPK performance.